Perempuan dalam Jaringan Radikalisme vis a vis Terorisme Global - Moh Rasyid (MUWAZAH : jurnal kajian gender, 2018)
This paper discusses about women in the framework of a global radical network on behalf of Islam as the basis of their struggle. This study uses a qualitative approach, with data sources from mass media and electronic media (newspapers, television, social media, etc.). Data collection techniques using document study. Analysis techniques use content analysis. The results show that women's involvement in the terrorist movement has been identified since the 1970s, where women became bombers after being brainwashed by male terrorists. Factors that led to the involvement of women in the global terrorism network, namely: 1) as an escape because of the discriminatory treatment that befell them; 2) reasons for concern over the inequalities suffered by the global Muslim community; 3) narrow religious awareness so that by becoming terrorists they feel they have the same social position as male terrorists in jihad; 4) psychologically unstable because of problems, and they surf on social media, so they are vulnerable to being trapped as terrorists and; 5) women whose husbands become terrorists are also involved as terrorists. The strategy carried out by terrorist groups in conquering women is by marrying them, even marrying them through social media that is legalized and / or legalized, so that according to the husband's wishes.